Long Term Care: Policy and Practice Outcomes. (11th November 2018) - Quach, E; Zhao, S; Kazis, L; Clark, V; McDannold, S; Hartmann, C
Abstract: Staff values, beliefs, and attitudes about resident safety (i.e., safety climate) are a key driver of resident safety in nursing homes. Staff with longer tenure may possess a richer understanding of resident safety. We investigated the association of staff tenure in years with safety climate, to further understand the potential impacts of staff retention policies. 56 Veterans Affairs Community Living Centers (CLCs, i.e., nursing homes) were sampled nationally to participate in the well-established and previously-validated CLC Employee Survey of Attitudes about Resident Safety (CESARS); 1, 396 staff participated. We used mixed random effect models with "individual attitudes towards safety" and "senior managers' commitment to safety" as the dependent variables and tenure in years as the key independent variable, controlling for VA facility complexity, staff occupation, shift, and full-time/part-time status, as well as clustering effects (by VA hospital, VA service network, and geographic region). Staff with longer tenure in the CLC showed more familiarity and felt more comfort and personal responsibility towards resident safety than staff with shorter tenure (p<0.0001). Yet staff with longer tenure perceived their senior managers' role as less active (p<0.01). Results indicate successful retention of staff may foster a higher personal commitment to resident safety, possibly by allowing staff to gain more learning opportunities, thus enriching their safety understanding. Although longer-tenured staff are more skeptical of senior managers' contributions to resident safety, when compared with their own, harnessing these staff's understanding of resident safety may be instrumental when designing nursing home safety interventions.